2009
DOI: 10.1002/qua.22341
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio investigation of water clusters (H2O)n (n = 2–34)

Abstract: ABSTRACT:Various properties of typical structures of water clusters in the n ϭ 2-34 size regime with the change of cluster size have been systematically explored. Full optimizations are carried out for the structures presented in this article at the HartreeFock (HF) level using the 6-31G(d) basis set by taking into account the positions of all atoms within the cluster. The influence of the HF level on the results has been reflected by the comparison between the binding energies of (H 2 O) n (n ϭ 2-6, 8,11,13,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…Dipole moments and orbital energy distribution (projected density of states) of the individual water molecules in these clusters were obtained with the same analysis methods as for the liquid water snapshots. The initial cluster geometries were taken from Qian et al [36].…”
Section: Property Calculationsmentioning
confidence: 99%
“…Dipole moments and orbital energy distribution (projected density of states) of the individual water molecules in these clusters were obtained with the same analysis methods as for the liquid water snapshots. The initial cluster geometries were taken from Qian et al [36].…”
Section: Property Calculationsmentioning
confidence: 99%
“…Their structure has been taken from the literature 45 and the geometries were reoptimized with the DFT functional and basis set indicated above. They are depicted on Figure 1; the actual Cartesian coordinates are given in the Supplementary material.…”
Section: The Calculationsmentioning
confidence: 99%
“…Such water monomers could be named centrally for-coordinated water (C4CW). Previous studies have reported the structure of larger water clusters [125][126][127][128][129][130]. For n > 6 cases, all the water monomers would form the surface of the cluster, until it comes n = 17 or more, when stable structures with odd-numbered molecules are C4CW clusters.…”
Section: Electronic Delocalization In H-bond Systemsmentioning
confidence: 99%